Improving equity in resource allocation in the Irish health service - O'Loughlin, Rosalyn (Trinity College (Dublin, Ireland). Department of Public Health and Primary Care, 2004)
Health systems worldwide are moving towards making their systems more transparent and more equitable, often due to pressure from consumers. Reforms to resource allocation systems are one attempt to do this. The nature of these reforms is varied but several are based on the concept of needs based weighted capitation models. The resource allocation system in Ireland's health service is non-transparent and is generally perceived as being inequitable. Due to the developments in other countries, Ireland can draw on their experiences to explore the options in relation to resource allocation reform. The aim of this study is to examine the desirability and feasibility of developing and introducing a more equitable alternative model for health care resource allocation in Ireland.
Keywords: Public Health, Ph.D.; Ph.D. Trinity College Dublin